Fighting Words : Imperial Censorship and the Russian Press, 1804-1906 - Ruud, Charles A., 1933- (Book collections on Project MUSE., 2009)
First published in 1982, Fighting Words focuses on the most common form of censorship in Imperial Russia: the governmental system that screened written works before or after publication to determine their acceptability.